Hepatic stellate cell-derived Delta-like 1 is dispensable for injury-induced liver fibrosis - Chen, Chunyi; Zhang, Maosen; Ma, Xian-Hua; Wang, Chen-Ma; Shi, Ya-Nan; Yuan, Jihong; Zhang, Weiping (Biochemical and biophysical research communications, 2025)
Chronic liver injury results in fibrosis and ultimately progresses to cirrhosis. Delta-like 1 (DLK1) has been implicated in the activation of myofibroblasts derived from hepatic stellate cells (HSCs) in the context of liver injury; however, the specific cellular origins of DLK1 remain a subject of debate. In this study, we demonstrate that DLK1 originating from HSCs is not essential for liver fibrosis resulting from chemical injury. The Dlk1 gene was expressed at comparable levels in primary hepatocytes and HSCs isolated from normal adult mice. Following liver injury induced by carbon tetrachloride (CCl4) intoxication, Dlk1 expression was markedly upregulated alongside the myofibroblast marker Pdgfrβ, α-SMA, and collagen genes in the liver. Conditional deletion of the Dlk1 gene in HSCs via Pdgfrb-Cre-mediated recombination did not significantly alter Dlk1 expression levels in either normal or injured whole liver. Importantly, the absence of Dlk1 in HSCs did not affect the elevation of plasma transaminases, hepatocyte proliferation, or Pdgfrβ activation during CCl4-induced acute liver injury. Moreover, during chronic liver injury and fibrosis, the loss of Dlk1 in HSCs did not influence HSCs activation, collagen deposition, or the expression of collagen genes (Col1a, Col3a). Collectively, our findings suggest that HSC-derived DLK1 is not critical for the activation of myofibroblasts and liver fibrosis. •Dlk1 gene is activated in fibrotic liver.•Deletion of HSC-derived Dlk1 does not affect Dlk1 levels in the liver.•HSC-derived Dlk1 is not essential for injury-induced liver fibrosis.